Assessment of Stereological Equations for Mineral Processing - Stephen Gay; Dewetia Latti (International Mineral Processing Congress, 2003)
"When improving a plant a mineral processing engineer would like to know the mineral composition distribution. In order to assess this distribution in particles, as compared to the corresponding distribution in particle sections, a procedure needs to be applied to the observed particle sections. Such a procedure is called a stereological correction. There exists many stereological correction procedures, but one group of such procedures is based on using those stereological equations that do not require making assumptions regarding particle shape or texture.In particular Davy derived an equation to estimate the covariance of mineral composition distributions for particles from both particle sections and linear intercepts. Furthermore, this covariance can also be used to measure the variance of the composition distribution of each mineral.This paper shall present results verifying this equation. The experimental method was based on obtaining particle information from serially-sectioned particles. Particle samples selected for serial sectioning displayed a range of natural textures including liberated, binary and composite particles. The exposed surface of the polished sections were analysed using QEM*SEM. This procedure was repeated until all of the grains have been polished away. The covariance of mineral distributions were calculated from the serial sections and compared with that calculated using Davy’s equation."